Resting ECG findings in elite football players - Bohm, P.; Ditzel, R.; Ditzel, H.; Urhausen, A.; Meyer, T (Journal of Sports Sciences, 2013)
The purpose of the study was to evaluate ECG abnormalities in a large sample of elite football players. Data from 566 elite male football players (57 of them of African origin) above 16 years of age were screened retrospectively (age: 20.9 ± 5.3 years; BMI: 22.9 ± 1.7 kg · m-2, training history: 13.8 ± 4.7 years). The resting ECGs were analysed and classified according to the most current ECG categorisation of the European Society of Cardiology (ESC) (2010) and a classification of Pelliccia et al. (2000) in order to assess the impact of the new ESC-approach. According to the classification of Pelliccia, 52.5% showed mildly abnormal ECG patterns and 12% were classified as distinctly abnormal ECG patterns. According to the classification of the ESC, 33.7% showed `uncommon ECG patterns`. Short-QT interval was the most frequent ECG pattern in this group (41.9%), followed by a shortened PR-interval (19.9%). When assessed with a QTc cut-off-point of 340 ms (instead of 360 ms), only 22.2% would have had `uncommon ECG patterns`. Resting ECG changes amongst elite football players are common. Adjustment of the ESC criteria by adapting proposed time limits for the ECG (e.g. QTc, PR) should further reduce the rate of false-positive results.